Stimulasi Kemampuan Berpikir Matematis Dalam Fisika Melalui Media Sosial - Fathan Nurfina Istiqomah, Hanin; Hendra Wijaya, Sugeng (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Muhammadiyah Sinjai, 2023)
Physics learning at university level uses social media as a learning media. This research was conducted to determine the effect of social media in stimulating mathematical thinking skills on physics at university level. This research is a quantitative research and One Group Pretest-Posttest Design as data collection. A total of 20 students were selected by purposive sampling method as participants. Smartphone is used as a learning media and WhatsApp has choosen as social media to support physics learning. International Phonetic Alphabet (IPA) Keyboard and Math Keyboard installed on the WhatsApp to stimulate mathematics and symbols in Physics equations. The learning approach applied is problem based-learning (PBL) with Kinematics materials. The results showed that there was an increase in the stimulation of students' mathematical thinking skills before and after using WhatsApp as social media with additional features Math Keyboard and IPA Keyboard. Thus, social media can be used to improve mathematical thinking skills on Physics